The Case for Licensure of Applied Behavior Analysts - Dorsey, Michael F (ABA International, 2009)
The evolution of the field of applied behavior analysis to a practice-oriented profession has created the need to ensure that the consumers of these services are adequately protected. We review the limitations of the current board certification process and present a rationale for the establishment of licensing standards for applied behavior analysts on a state-by-state basis. Recommendations for securing the passage of a licensure bill also are discussed.